Kameleon w egzegezie biblijnej św. Hieronima - Krzyszczuk, Łukasz (Verbum Vitae, 2017)
This article shows how Jerome employed information about flora and fauna derived from the works of naturalists in the case of the chameleon, an exotic animal mentioned in his Commentary on Zephaniah, written in 393. In his allegorical explanation of Zep 2:12-15, the Bethlehem-based monk compared the color-changing ability of the chameleon to the sinful conduct of the hypocrites, who only pretend to be Christians. Since Jerome’s biblical commentaries are consistent with the larger exegetical tradition of the era, the testimonies of other Christian authors have been invoked as well. This allows us to trace, within the exegesis of the Greek Fathers of the Church, the sources of Jerome’s commentaries on the Prophetic Books of the Old Testament.